Sports achievements and morphometric characteristics of Oldenburg horse lines - I. Suprun; V. Turchenko (Тваринництво та технології харчових продуктів, 2024)
The Oldenburg horse breed, due to its versatility, is a promising object for scientific research. Identification of regular relationships between genealogical characteristics, morphometric indicators and athletic achievements of representatives of this breed is critical for the development of effective breeding programmes. The purpose of the study was to analyse the influence of line affiliation on the morphological characteristics and athletic performance of Oldenburg horses and to identify links between morphological traits and athletic performance. The study was conducted at the equestrian complex “Schockemoehle” (Germany), including 90 Oldenburg horses, divided by sex and lineage. Morphometric indicators and sports achievements are analysed. The results show the dominance of the Cor de la Bryere lineage (48.9% of the total sample), which indicates the success of breeding programmes in improving its characteristics. Other significant lines had a share of 15.6% to 10.0% in the sample structure. Morphometric analysis showed high uniformity among horses in height at the withers and metacarpal circumference, with slight differences between the sex groups: height at the withers ranges from 168.13 cm to 169.2 cm, and metacarpal circumference – from 20.85 cm to 20.99 cm. Analysis of sporting achievements showed that geldings are highly effective in overcoming high obstacles, reaching the Grand Prix level (≥155 cm) in 23% of cases, compared to 10% among stallions and mares. Stallions and mares usually reach the level of 130-140 cm, with some predominance of mares in this category. The study of different lines shows that the Diamant de Semilly and Almé Z lines have advantages in morphometric parameters, such as height at the withers and metacarpal circumference, which can affect athletic performance. The Capitol I line has the largest number of competitions, but needs to be improved to achieve better athletic performance. The practical significance of the results lies in the possibility of optimising the breeding strategies of sports horses to achieve better achievements in competitions